Exploring the Selfie Historical, Theoretical, and Analytical Approaches to Digital Self-Photography (Springer International Publishing, 2018)
This volume explores the selfie not only as a specific photographic practice that is deeply rooted in digital culture, but also how it is understood in relation to other media of self-portrayal. Unlike the public debate about the dangers of 'selfie-narcissism', this anthology discusses what the practice of taking and sharing selfies can tell us about media culture today: can the selfie be critiqued as an image or rather as a social practice? What are the technological conditions of this form of vernacular photography? By gathering articles from the fields of media studies; art history; cultural studies; visual studies; philosophy; sociology and ethnography, this book provides a media archaeological perspective that highlights the relevance of the selfie as a stereotypical as well as creative practice of dealing with ourselves in relation to technology.